2018
DOI: 10.1016/j.clinbiomech.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of shoulder compressive and shear forces during functional activities of daily life

Abstract: This study demonstrates substantial loads through the glenohumeral joint during activities of daily living. The ratios of glenohumeral shear force component to compression force component are considerable when high loads act at long lever arms and at high angles of arm elevation. These glenohumeral ratios represent a key component of loading that should be considered when designing implants, surgical procedures, or rehabilitation protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 43 publications
1
30
0
2
Order By: Relevance
“…Biomechanically, the shorter is the lever arm, the less is the load moment [14,26]. When a cortical screw is inserted to maintain the syndesmotic stability, the screw becomes the fulcrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomechanically, the shorter is the lever arm, the less is the load moment [14,26]. When a cortical screw is inserted to maintain the syndesmotic stability, the screw becomes the fulcrum.…”
Section: Discussionmentioning
confidence: 99%
“…The far is a screw from the point of load application (i.e. anteromedial aspect of the lateral malleolus), the bigger is its loading stresses [14]. In other words, a more proximally placed screw will sustain more bending and rotational stresses.…”
Section: Introductionmentioning
confidence: 99%
“…All subjects were instructed to perform sixteen functional activities of daily living with three sets per activity ( Table 2). 28 Kinematic data collection was performed using a 10-camera optical motion tracking system (Vicon Motion Tracking System, Oxford, UK) with three load cells (Kistler Type 9286B, Kistler Instrument Corp., Winterthur, Switzerland).…”
Section: Experimental Datamentioning
confidence: 99%
“…2 For each subject, data were normalised based on maximum EMG signals during maximum voluntary contraction tests. 2 The muscle force predictions of the MRI-based and linearly scaled-generic models were analysed as described in Klemt et al 28 In brief, once the start and end point of each functional activity was established, the muscle forces and joint forces were quantified at each time point. Interpolation using a cubic spline function was used to allow comparison between measurements for different activities and trials by representing each of them by 100 time points.…”
Section: Evaluation Of Generic and Mri-based Modelsmentioning
confidence: 99%
“…While it is understood that supraspinatus initiates abduction, the pull-up activity is essentially loaded adduction, where supraspinatus acts in the mid-range to keep the humeral head compressed into the glenoid fossa. 32 Additionally, proprioceptive Type IV mechanoreceptors within the rotator cuff muscles and tendons may also act in anticipation of pending initiation of motion. 28,33 In contrast to the results here, Youdas et al 4 found the reverse grip more effective at activating biceps brachii, compared to a front grip.…”
mentioning
confidence: 99%